Pengaruh Penerapan Prinsip-Prinsip Good Governance Terhadap Keberhasilan Penerapan Penganggaran Berbasis Kinerja APBD Kabupaten/Kota Se-Wilayah III Cirebon Dengan Komitmen Organisasi Sebagai Variabel Moderator - Dadang Suhendar (Program Studi Akuntansi, Universitas Kuningan, 2016)
The purpose of this study are to analysis; the influence of the implementation good govenance principles toward succesess the implementation ferpormance based budgeting APBD Kabupate/Kota Se-Wilayah III Cirebon with komitmen organisasi as moderatory variable. The reaserch sample are collecting with purposive methode. The reaserch methode are descriptive and verificative and analysis methode used multiple regression. The result of study show that implementation of good governance principles with organization commitment have significant impluence to succes implementations performance based budgeting APBD,but commitment organization as moderatory variable is’nt influence to succes implementation of performance based budgeting APBD. Keyword ; Good Governance Principles (tranfarancy, participacy, acountability), Performance Based Budgeting APBD, and Organization Commitment.